2004
DOI: 10.1103/physrevb.70.220505
|View full text |Cite
|
Sign up to set email alerts
|

Current carrying ground state in a bilayer model of strongly correlated systems

Abstract: Strongly interacting systems have been conjectured to spontaneously develop current carrying ground states under certain conditions. We conclusively demonstrate the existence of a commensurate staggered interlayer current phase in a bi-layer model by using the recently discovered quantum Monte-Carlo algorithm without the sign problem. A pseudospin SU(2) algebra and the corresponding anisotropic spin-1 Heisenberg model are constructed to show the competition among the staggered interlayer current, rung singlet … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…To access the quantum critical behavior of the CDW transition induced by repulsions, it is desired to simulate the interacting model using fermion-sign-free QMC on lattices with relatively-large size. Nonetheless, conventional auxiliary-field QMC simulations of interacting spinless fermion model generally suffer from the fermion-sign problem because the usual strategies [37][38][39][40][41][42][43][44][45][46] employed in auxiliary-field QMC for solving fermion-sign problem of even species of fermions do not directly work. Recently, we discovered that certain interacting spinless fermion systems can be studied by fermion-sign-free QMC employing Majorana representation [1].…”
Section: The Mqmc Methodsmentioning
confidence: 99%
“…To access the quantum critical behavior of the CDW transition induced by repulsions, it is desired to simulate the interacting model using fermion-sign-free QMC on lattices with relatively-large size. Nonetheless, conventional auxiliary-field QMC simulations of interacting spinless fermion model generally suffer from the fermion-sign problem because the usual strategies [37][38][39][40][41][42][43][44][45][46] employed in auxiliary-field QMC for solving fermion-sign problem of even species of fermions do not directly work. Recently, we discovered that certain interacting spinless fermion systems can be studied by fermion-sign-free QMC employing Majorana representation [1].…”
Section: The Mqmc Methodsmentioning
confidence: 99%
“…We rationalise these findings based on large-coupling effective theories 17 . In a related Hubbard model with both interlayer density interactions and interlayer Heisenberg exchange, a previous QMC study 18 revealed the existence of a current-carrying phase. But also therein, the sign problem confined the explorable parameter space, and the interaction range that we consider here has not be explored in that previous study.…”
Section: Introductionmentioning
confidence: 97%
“…[25][26][27][28] The effect of correlations in conjunction with frustration has been investigated for models of fermions and quantum spins. 20,22,[29][30][31][32][33][34][35][36] In both cases, analogs of the CSF state are obtained as staggered current (for fermions) or gapless chiral (for spins) states. An analog of the CMI state has been found for fermions in a ladder model.…”
Section: Introductionmentioning
confidence: 99%